Initiated by organic peroxides cooligomerization of unsaturated hydrocarbons of C5 fraction – by-product of ethylene production - Dzinyak, Bohdan; Melnyk, Stepan (Publishing House of Lviv Polytechnic National University, 2016)
Initiated by organic peroxides cooligomerization of unsaturated compounds of C5 fraction has been studied. Such fraction is a by-product obtained at ethylene production via hydrocarbon raw material pyrolysis. The main regularities of the process have been established, the effect of main factors (temperature, reaction time, nature and concentration of the initiators) on the yield and physico-chemical characteristics of the obtained cooligomers has been examined. The effective initiator and optimal technological parameters of the cooligomerization process have been determined. Робота присвячена дослідженню ініційованої органічними пероксидами коолігомеризації суміші ненасичених сполук, що містяться у фракції С5 – побічному продукті виробництва етилену піролізом вуглеводневої сировини. Встановлено основні закономірності коолігомеризації ненасичених вуглеводнів фракції С5. З’ясовано характер впливу основних чинників (температури, тривалості реакції, природи та концентрації ініціаторів) на вихід і фізико-хімічні характеристики одержаних коолігомерів. Вибрано ефективний ініціатор коолігомеризації та оптимальні технологічні параметри процесу.
Ініційована органічними пероксидами коолігомеризація ненасичених вуглеводнів фракції С5 – побічного продукту виробництва етилену
Keywords: pyrolysis liquid product; hydrocarbon; peroxide; petroleum resin; cooligomerization; рідкі продукти піролізу; вуглеводні; пероксид; нафтополімерна смола; коолігомеризація